Empowering Santripreneurs through Sharia Economic Principles at Pondok Pesantren Hidayatush Sholihin in Sambas Regency - Nurjannah, Syamratun; Helvira, Reni; Zulinda, Nia; Nurhayati, Nurhayati (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
This Community Service program aims to empower students at Pondok Pesantren Hidayatush Sholihin in Sambas Regency by integrating Sharia economic principles into entrepreneurship training. Utilizing a Service Learning (SL) approach, the program combined theoretical instruction with practical business activities rooted in Islamic values. It was implemented through three structured phases: preparation, implementation, and evaluation. Activities included needs assessment, interactive workshops, business simulations, and mini-projects facilitated by expert trainers. The program significantly enhanced the santri’s understanding of Sharia-based entrepreneurship, as demonstrated by their ability to develop ethical business plans, manage finances, and apply digital marketing strategies. The initiative also strengthened institutional capacity, promoted ethical economic practices, and fostered social responsibility. These outcomes illustrate the real impact of the program in producing competent, values-driven santripreneurs and offer a replicable model for pesantren-based economic empowerment.